0 0

# 4(x - 1) - (x + 6) = 2

please help im confused

Tutors, please sign in to answer this question.

### 2 Answers

First, look at the terms, you have two instances of x and the rest of the terms are numbers. Since there aren't any other letters, this tells you that in this problem, x is an unknown, not a variable. You must isolate x on one side and that will give you the value of x.

Break up the problem into small pieces. When you see parenthesis and a number in front, that indicates that you must use the distribution property. There are two instances of this.

4(x - 1) + (-1)(x + 6) = 2

Distribute the 4

4x - 4 + (-1)(x + 6) = 2

Distrubte the -1

4x - 4 - x - 6 = 2

Now rearrange terms. You can do this because you can add a bunch of numbers in any order you want

4x - x - 4 - 6 = 2

Combine like terms, those with an x and those without.

3x - 10 = 2

Add 10 to both sides to remove it from the left side.

10 + 3x - 10 = 2 + 10

3x = 12

And finally, isolate x by dividing both sides of the equation by 3

x = 4

And there you have it! See, break it up into tiny pieces and the problem becomes much easier.

4 ( x - 1 ) - ( x + 6 ) = 2

multiply 4 by ( x - 1 )

( 4x - 4 ) - ( x + 6 ) = 2

open the bracket

4x - 4 - x - 6 = 2

collect  like terms

4x - x - 4 - 6 = 2

add up like terms

3x - 10 = 2

make x the subject of formula

3x = 2 + 10

3x = 12

divide both sides by 3

x = 4

you are done!